Outcome of immediate postpartum intrauterine contraceptive device in caesarean versus vaginal insertion: a comparative study - Shanavas, Aswathy; Jacob, Sujamol; Chellamma, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Immediate Postpartum Intrauterine Contraceptive device is a novel approach to contraception which integrates Maternal - Child health and family planning services. It is a postpartum method which provides long term reversible contraception to women before discharge from the delivery setting. More research is needed in the field of PPIUCD to enhance awareness and acceptance in the community. This study is designed to compare the safety and efficacy of PPIUCD inserted at cesarean versus vaginal delivery. Methods: This is a prospective study conducted at Sree Avittom Thirunal Hospital, Govt. Medical College, and Kerala – A tertiary care teaching institution. A total of 126 patients with cesarean or vaginal deliveries had PPIUCD insertions and they were followed up for a period of one year. The outcome measures analyzed were safety measures – menstrual irregularities, vaginal discharge, pelvic infection and perforation and efficacy measures - failure, expulsion and removal. Data are expressed in frequency and percentage. Chi square test was used for comparison and P value <0.05 was considered significant. Results: The study shows that PPIUCD is an effective intervention in both cesarean and vaginal delivery with no significant differences in safety and efficacy depending on the route of insertion. There was no case of perforation or failure and no significant risk of infection in either group. Spontaneous expulsion occurred in two cases inserted by vaginal route. Missing string incidence is high in the cesarean group compared to vaginal insertion. Conclusions: PPIUCD is a safe effective and convenient method of contraception and should be encouraged in both vaginal and cesarean deliveries.